How Technology Readiness and Entrepreneurial Orientation Shape MSME Marketing Performance in Cirebon City, Indonesia - Siska Ernawati Fatimah; Badrudin Hadibrata (Yayasan Sinergi Kawula Muda, 2026)
Many MSMEs now rely on digital technology in their everyday marketing activities, especially to reach customers and promote their products more efficiently. Using digital media, businesses can reach customers more easily, introduce products, and keep in touch with buyers. However, not all MSMEs get better marketing results from using technology. A main reason is that many businesses are not ready to use technology well in their work. While many studies have examined digital adoption and the entrepreneurial mindset, few have examined how readiness to adopt technology affects marketing success in MSMEs. This study examines how technology readiness and an entrepreneurial mindset impact marketing outcomes. It also examines whether an entrepreneurial mindset alters the effect of technology readiness on marketing success. The study collected data from 180 MSME owners and managers in Cirebon City, Indonesia. Participants were selected deliberately, and information was collected through questionnaires. The data were analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results show that being ready to adopt technology is strongly linked to better marketing results. Having an entrepreneurial mindset also helps marketing success. However, the idea that an entrepreneurial mindset changes the effect of technology readiness was not supported. This means that being ready to use technology directly improves marketing results, regardless of entrepreneurial mindset. The findings show that digital marketing success in MSMEs depends heavily on how ready businesses are to use technology in their operations and decision-making.